Geometric nonlinear vibration analysis of steel frames with semi-rigid connections and rigid-zones - Anh, Vu Quoc; Hien, Nghiem Manh (Vietnam Journal of Mechanics, 2003)
To obtain an accurate insight into the behavior of the most realistic steel frames, joint flexibility should be allowed for in the analysis. So far, most research work is concentrated on the linear and geometric nonlinear static analysis of steel frames with flexible connections. Very few papers were contributed to the dynamic and vibration analysis of these types of frames. This paper proposes a numerical method for geometric nonlinear vibration analysis of frames with semi-rigid connections and rigid-zones. The effect of initial stress due to the applied load is accounted for in the suggested method, which is believed to be more general than the existing methods and does not involve complex calculations.